MONTE CARLO-BASED UNCERTAINTY ANALYSIS OF NON-IDEAL BIDIRECTIONAL DC-DC CONVERTER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Bidirectional DC-DC converters are widely employed in DC bus-based power systems that supply resistive DC loads due to their simple structure and inherent capability for bidirectional power flow. This paper presents a comprehensive Monte Carlo-based uncertainty analysis of a non-ideal bidirectional DC-DC converter operating with a resistive DC load. Inductor and capacitor tolerances, parasitic resistances, and component operating temperature uncertainties are simultaneously randomized to assess their combined impact on DC bus voltage regulation during bidirectional operation. Simulation results confirm that the bidirectional converter maintains stable operation and bounded performance dispersion under parametric uncertainties. The proposed framework provides a robustness-oriented evaluation methodology that complements conventional deterministic analysis for DC bus-interfaced power converters.
Keywords: Monte Carlo simulation; Uncertainty analysis; Bidirectional DC-DC converter; Non-ideal converter